Análise termodinâmica do movimento de corpos em meios dissipativos: uma aplicação do Teorema de Gouy–Stodola - Cardoso, Daniel (Universidade Federal de São Carlos, 2025)
This work presents a thermodynamic analysis of energy dissipation and entropy generation in the falling motion of bodies immersed in viscous fluids, using the Gouy–Stodola Theorem as the central framework. Based on the First and Second Laws of Thermodynamics, the study investigates how dissipative forces — modeled by linear or quadratic drag — limit the conversion of mechanical energy into useful work. Experiments were conducted with three geometries (sphere, cube, and drop) in two media (water and glycerin) to determine terminal velocities and estimate drag coefficients. Using data obtained through video analysis, the dissipated power and the rate of entropy generation over time were quantified. The equations of motion were derived and interpreted in light of thermodynamic admissibility, allowing the identification of regions in phase space consistent with positive entropy production. The results show that the thermodynamic approach enhances the understanding of dissipative mechanical systems by rigorously integrating the concepts of irreversibility and entropy into the analysis of motion.
Thermodynamic analysis of the motion of bodies in dissipative media: an application of the Gouy–Stodola Theorem
Keywords: Termodinâmica; Geração de Entropia; Força de Arrasto; Teorema de Gouy-Stodola; Sistemas Dissipativos; Termodynamics; Entropy Generation; Gouy-Stodola Theorem; Drag Force; Dissipative Systems; CIENCIAS EXATAS E DA TERRA::FISICA; 4. Educação de Qualidade